2017
DOI: 10.1080/10826084.2017.1334064
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of Tobacco Use Among People Living With HIV in Puerto Rico

Abstract: Findings highlight the need for smoking cessation strategies in this population, particularly among male HIV+ drug users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A previous study among HIV-positive men and women 18 years and older receiving HIV care in PR reported a similar prevalence of current cigarette use (29.0%) and daily smoking was reported in 76.7% of them. 38 Further studies should assess robust smoking indicators to understand better the impact of smoking, including frequency and number of cigarettes, on anal HSIL among HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study among HIV-positive men and women 18 years and older receiving HIV care in PR reported a similar prevalence of current cigarette use (29.0%) and daily smoking was reported in 76.7% of them. 38 Further studies should assess robust smoking indicators to understand better the impact of smoking, including frequency and number of cigarettes, on anal HSIL among HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%